Imprisonment as Punishment for Children Support Arrears in Syariah Court - Ismail, Mohd Hazwan (Kanun: Jurnal Undang-undang Malaysia; Vol 36 No 1 (2024): Kanun: Jurnal Undang-undang Malaysia Volume 36 Number 1 January 2024, 2023)
Child support arrears occur after a court order. In legal principle, the starting point for arrears is one month after the minimum period. As the creditor, the mother will then file a complaint before the judge to recover the unpaid child support. In the prison sentence of the debtor, or father, the provision of the law is initiated by the Judgment Debtor Summons, followed by the Judgment Notice if there is still arrears after being ordered from the Judgment Debtor Summons. The research question arises when the Shariah has stipulated that the prison sentence imposed on cases of child support arrears is for a period not exceeding 30 days and must be separated for arrears (civil) with criminal offenses. This is done to determine whether Malaysian legal provisions adhere to Islamic law. The method employed in this study is data collection from library research and fieldwork. Additionally, interview method was used to support the research. Statistical information was also obtained to describe the registration of cases that occur in Malaysia. The findings of this study revealed that the imprisonment term imposed on debtors is in line with Shariah whenever the Syariah Court Civil Procedure (Federal Territories) Act 1998 calls for a sentence of no more than 30 days. The segregation of prison sentences between criminal offenses and civil offenses is not practiced in Malaysia because the law in Malaysia has stipulated in the Prison Act 1995 that the two offenses are concurrent and not segregated. Keywords : Imprisonment, arrears of maintenance, Judgment Debtor Summons, Judgment Notice, legislation, Syariah Court Fullt text : PDF